Pengaruh Lingkungan, Kompensasi, dan Disiplin terhadap Loyalitas Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada Restaurant Combine Steak dan Omah Duren Kavling DPR Sidoarjo - Dianita Retno Widyastuti; Budi Prabowo (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to determine how the influence of Environment, Compensation, and Discipline on Employee Loyalty with Job Satisfaction as an intervening variable at Restaurant Combine Steak and Omah Duren Kavling of DPR Sidoarjo. The type of this research is descriptive quantitative research, while the population sample in this research is all employees of Restaurant Combine Steak and Omah Duren, totaling 35 employees. Data was collected using a questionnaire. The analysis technique for this research was using Path Analysis using the SPSS version 25 program.Based on the results of this study it was concluded that work environment and work discipline have a significant effect on job satisfaction, compensation has no significant effect on job satisfaction, work environment, compensation and work discipline have a significant effect on work loyalty, while job satisfaction has no significant effect on employee loyalty. Keywords: Environment, Compensation, Work Discipline, Employee Loyalty, Job Satisfaction